Characterisation of a putative agr system in Clostridium botulinum and Clostridium sporogenes - Cooksley, Clare Marie (2008)
Botulinum neurotoxin induces a potentially fatal paralytic condition in humans and various animal species collectively known as 'botulism'. It consequently poses a major problem to the food industry, due to the ability of its spores to survive in cooked foods. The incidence of wound botulism has also suffered a recent increase in the UK. The genome sequence of the C botulinum Group I strain ATCC 3502 has recently been determined. In silico analysis has revealed the presence of two distinct loci capable of encoding proteins with homology to AgrB and AgrD of the Staphylococcus aureus agr quorum sensing system. The functional characterisation of these genes has been carried out in order to determine whether they play a role in quorum sensing. To simplify laboratory procedures, C. sporogenes, the non-toxic counterpart of C. botulinum, was initially focused on. The agr regions in C. sporogenes were sequenced and their proteins compared with those of C. botulinum and other Gram-positive bacteria. Regions of conservation were observed amongst the clostridia and, to a lesser extent, between clostridia and staphylococci.